La Segunda Guerra Mundial en NO-DO: un comienzo germanófilo (de enero a julio de 1943) - Rodríguez Sánchez, Mercedes (Derecom. Revista Internacional de Derecho de la Comunicación y de las Nuevas Tecnologías, 2024)
The present paper is the result of an investigation into the Spanish newsreel NO-DO that aims to shed some light on the political and propaganda purposes that led the Franco Regime to create a weekly, official and mandatory newsreel in 1942. It held the monopoly of cinematographic information throughout the dictatorship. The main goal of this essay is to highlight the role that NO-DO played in the Francoist propaganda network, immersed in a context of tight governmental control over the Media, focusing on the analysis of World War II coverage made by the Spanish newsreel.The first NO-DO newsreel, created by the Order of December 17, 1942, was screened on January 4, 1943, when the balances of World War II forces began to change in favour of the Allies and the Head of the Spanish Government, Francisco Franco, had left behind two major internal crises in less than eighteen months and, beyond the difficulties arising from the international conjuncture, his position within the country was increasingly strong. From then until the end of the war, the advance of the Allied troops marked the political and informative agenda of Franco’s government, especially at international level, since it had to face strong pressure from Great Britain and the United States, as well as from monarchical and republican oppositions in exile.